Targeting potential receptor molecules in non-small cell lung cancer (NSCLC) using in silico approaches - Kirubhanand, C.; Merciline Leonora, J.; Anitha, S.; Sangeetha, R.; Nachammai, K. T.; Langeswaran, K.; Gowtham Kumar, S. (Frontiers in Molecular Biosciences, 2023)
The title molecule, lochnericine, was optimized, and structural parameters were measured in this study. The vibrational molecule spectra showed a strong correlation with previously published experimental results. Using Frontier Molecular Orbital (FMO), the calculated band gap energy value associated with bioactive compounds and the molecule's potential bioactivity is confirmed. The H38 hydrogen atom and O1 oxygen atom in the molecule are effectively electrophilic, and potential nucleophilic attack sites were confirmed through analysis of the Molecular electrostatic potential surface. Furthermore, the electrons within the molecule were delocalized, which confers bioactivity on the title molecule and was authorized through Mulliken atomic charge distribution analysis. A molecular docking study revealed that lochnericine inhibits non-small cell lung cancer-associated targeted protein. The lead molecule and targeted protein complex were stable during molecular dynamics simulation studies till the simulation period. Further, lochnericine demonstrated remarkable anti-proliferative and apoptotic features against A549 lung cancer cells. The current investigation powerfully suggests that lochnericine is a potential candidate for lung cancer.